Clonal growth in plants : regulation and function / J. Van Groenendael; H. de Kroon - Van Groenendael, Jan; Kroon, Hans de (The Hague SPB Academic Publishing, 1990)
Clonal plants are dominant constituents of many ecosystems. Consequently, the structure and species composition of the vegetation is largely determined by processes that govern clonal growth. In this book emphasis is placed on two fundamental aspects of clonality. The first part of the book focuses on the various mechanisms that regulate clonal growth including ontogenetic development, resource transport and hormonal control, supplemented with information on the phylogenetic origin of clonality. The second part considers the ecological and evolutionary significance of clonal groth characteristics such as physiological integration, meristem differentiation and morphological plasticity. The volume compiles up-to-date reviews of these topics and points out areas which have been poorly represented in the literature so far. It seeks to bridge the gap between physiologists, plant morphologists and (evolutionary) plant ecologists by suggesting integrated research approaches. It should appeal to both graduate students and to experienced scientists working in these fields.
Contenido: Part 1. Regulation Part 2. Function Taxonomic index, Subject index
Keywords: Clonacion; Fisiologia Vegetal; Reproduccion Asexual